Sex‐Related Differences in Patients at High Bleeding Risk Undergoing Percutaneous Coronary Intervention: A Patient‐Level Pooled Analysis From 4 Postapproval Studies. Issue 7 (9th April 2020) - Chandiramani, Rishi; Cao, Davide; Claessen, Bimmer E.; Sorrentino, Sabato; Guedeney, Paul; Blum, Moritz; Goel, Ridhima; Roumeliotis, Anastasios; Krucoff, Mitchell; Kozuma, Ken; Ge, Junbo; Seth, Ashok; et al.
Abstract : Background: Women have been associated with higher rates of recurrent events after percutaneous coronary intervention than men, possibly attributable to advanced age at presentation and greater comorbidities. These factors also put women at higher risk of bleeding, which may influence therapeutic strategies and clinical outcomes. Methods and Results: We performed a patient‐level pooled analysis of 4 postapproval registries to evaluate sex‐related differences in patients at high bleeding risk (HBR) undergoing percutaneous coronary intervention. HBR required fulfillment of at least 1 major or 2 minor criteria of the Academic Research Consortium definition. Outcomes of interest were major bleeding and major adverse cardiac events (composite of cardiac death, myocardial infarction, or definite/probable stent thrombosis). Of the total 10 502 patients, 2832 (27.0%) were women. The prevalence of HBR was higher in women compared with men (29.0% versus 20.5%, P <0.0001). Women at HBR were older and had more comorbidities, while men at HBR were more often smokers, with prior myocardial infarction and more complex coronary lesions. At 4 years, women at HBR had significantly higher major bleeding compared with men at HBR (10.8% versus 6.2%, P <0.0001); however, this difference was attenuated after multivariable adjustment (hazard ratio, 0.92; 95% CI, 0.41–2.08). Major adverse cardiac event rates between groups were similar (12.2% versus 12.6%, P =0.82) and remained consistent after adjustment (hazard ratio, 0.64; 95% CI, 0.32–1.28). Conclusions: The prevalence of HBR was higher in women compared with men, with considerable differences in the distribution of criteria. Women at HBR experienced higher rates of major bleeding but similar major adverse cardiac event rates compared with men at HBR at 4 years.